Pengembangan Model Manajemen Layanan Informasi Karir Berbasis ICT Bagi Peserta Didik SMA - Yohanes Andang Darmawan; Yari Dwikurnaningsih (Jurnal Konseling dan Pendidikan, 2021)
Research problem formulation is how to develop career information services in high school to improve high school students' understanding of careers. Research Objectives include: (1) knowing career information services that have been carried out in high school; (2) describes the advantages and disadvantages of career information services in high school; (3) developing ICT-based career information service models for high school students. The research was designed based on the objectives to be achieved, the approach used to use the method of "research and development" (R&D) by following the pattern of stages of Borg and Gall research (2003). The trial was summarized into 3 main stages namely introduction, development and testing. The research trial was conducted in Salatiga with the research subjects being high school students. Data collection techniques using interviews, observation, and questionnaires. Data analysis uses quantitative and qualitative analysis. R & D results obtained by factual models, design models, and the final model is given the name of ICT-Based Career Information Service Management Model for High School Students. The name of the career information service program on the website is http //: tesbakat.top which contains: (1) self-exploration of interest and personality tests; (2) lecture exploration; (3) career exploration; (4) evaluation and self-reflection. The model is already suitable to use. Evidenced by the development of ICT-based career information management service management models can improve the career understanding of high school students.